Lysosomal cystine mobilization shapes the response of TORC1 and tissue growth to fasting. - Jouandin, P.; Marelja, Z.; Shih, Y.H.; Parkhitko, A.A.; Dambowsky, M.; Asara, J.M.; Nemazanyy, I.; Dibble, C.C.; Simons, M.; Perrimon, N. (Science, 2022)
Adaptation to nutrient scarcity involves an orchestrated response of metabolic and signaling pathways to maintain homeostasis. We find that in the fat body of fasting Drosophila, lysosomal export of cystine coordinates remobilization of internal nutrient stores with reactivation of the growth regulator target of rapamycin complex 1 (TORC1). Mechanistically, cystine was reduced to cysteine and metabolized to acetyl-coenzyme A (acetyl-CoA) by promoting CoA metabolism. In turn, acetyl-CoA retained carbons from alternative amino acids in the form of tricarboxylic acid cycle intermediates and restricted the availability of building blocks required for growth. This process limited TORC1 reactivation to maintain autophagy and allowed animals to cope with starvation periods. We propose that cysteine metabolism mediates a communication between lysosomes and mitochondria, highlighting how changes in diet divert the fate of an amino acid into a growth suppressive program.